2021
DOI: 10.1016/j.sjbs.2021.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Wonder or evil?: Multifaceted health hazards and health benefits of Cannabis sativa and its phytochemicals

Abstract: Cannabis sativa , widely known as ‘Marijuana’ poses a dilemma for being a blend of both good and bad medicinal effects. The historical use of Cannabis for both medicinal and recreational purposes suggests it to be a friendly plant. However, whether the misuse of Cannabis and the cannabinoids derived from it can hamper normal body physiology is a focus of ongoing research. On the one hand, there is enough evidence to suggest that misuse of marijuana can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 255 publications
(264 reference statements)
0
15
0
4
Order By: Relevance
“…ADHD is one of the most common neurodevelopmental behavioral disorders characterized by inattentiveness, hyperactivity, and impulsiveness ( Datta et al, 2021 ). It is found amongst 1 out of 20 children ( Pellow et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADHD is one of the most common neurodevelopmental behavioral disorders characterized by inattentiveness, hyperactivity, and impulsiveness ( Datta et al, 2021 ). It is found amongst 1 out of 20 children ( Pellow et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diet, elimination diets, nutritional supplements (for example, supplementation with essential fatty acids), homeopathy, yoga, exercise, massage, and botanicals have been tested against ADHD ( Pellow et al, 2011 ). Both single and multi-ingredient formulas have been reported effective in several studies, and combination therapies were found to be beneficial against cognitive and behavioral problems ( Rucklidge et al, 2009 ; Banerjee et al, 2021 ; Datta et al, 2021 ; Halder et al, 2021 ; Tandon et al, 2021 ). However, the safety and efficacy of CAM treatments, especially for children, need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Strong healing properties are indicated even among drug-resistant bacteria, such as the Staphylococcus aureus strain. Hemp also contains various polyphenols with antioxidant properties, coloring compounds and polysaccharides [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Characteristics Of Hemp Plantsmentioning
confidence: 99%
“…Plants produce various secondary metabolites and phytochemicals usually as a response to factors such as microbial invasion 170,171 . Phytochemicals are a group of such secondary metabolites that are naturally synthesized by plants and can be extracted and purified for medical use 172–177 . Natural compounds have beneficial properties like low cytotoxicity and epidemiological studies indicate the numerous health benefits they offer.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…170,171 Phytochemicals are a group of such secondary metabolites that are naturally synthesized by plants and can be extracted and purified for medical use. [172][173][174][175][176][177] Natural compounds have beneficial properties like low cytotoxicity and epidemiological studies indicate the numerous health benefits they offer. Therefore, a number of clinical studies have been performed with plant-derived natural products.…”
Section: Clinical Applicationsmentioning
confidence: 99%